Strategi Organisasi Kesehatan Masyarakat dalam Menangani Ketimpangan Akses Layanan Kesehatan di Indonesia - Solehah Aura Ramadhin br Sianipar Aura; Dinda Syahbania; Nayla Azzahra; Maysyarah Tanjung; Nabilah Risti Ameliya; Nasywa Azzahra Siregar; Dita Chania Tri Irsan; Fadillah Dwi Putri; Khairuna Pratiwi; Aulia Farah Dina; Rindi Artika; Dewi Agustina (Getpress Management Journals, 2025)
Inequity in access to healthcare services remains a major challenge within Indonesia’s national health system. Although the government has introduced various programs such as the National Health Insurance (JKN) and BPJS Health, disparities between urban and rural areas, as well as between affluent and low-income populations, are still clearly evident. This article aims to evaluate the strategies employed by public health organizations, both governmental and non-governmental, in addressing these disparities. The study uses a qualitative approach through literature review and policy analysis. The findings indicate that the effectiveness of these strategies is strongly influenced by cross-sector collaboration, data-based planning, and local community participation. However, challenges such as limited resources, shortages of healthcare workers in remote areas, and imbalanced health infrastructure remain significant barriers. Therefore, policy innovations that strengthen the role of public health organizations are needed to achieve equitable healthcare access in Indonesia.